MONARCHY REMOVING IN RIDLEY SCOTT'S GLADIATOR MOVIE (2000): A SOCIOLOGICAL APPROACH - RATNAWATI, ANIK (2011)
The objective of the study is to examine how monarchy removing is reflected in Ridley Scott's Gladiator based on sociological approach and the structural elements. It is done by establishing two objectives: the first is analyzing the movie based on its structural elements and the second is analyzing the movie based on the sociological approach. The research is conducted by using qualitative method. The object of the research is the movie entitled Gladiator directed by Ridley Scott. The writer uses two data sources namely primary and secondary data source. The primary data is movie Gladiator directed by Ridley Scott. The secondary data sources are the other sources related to the analysis like some books and internet. The method of the data collection is library research. The technique of data analysis is descriptive analysis. The results of the research show that: first, the Roman experience was once and still remaining a most important segment of the human story. Second, in Gladiator movie, Ridley Scott shows his view on politics that Monarchy is not suitable to be applied to manage a country and Republic is the most suitable because Republic respects the human right where every member of nation has right for live as free men with no slavery and the society have right to elect the leader of their nation. Third, Ridley Scott wants to say that slavery needs to be erased because it does not respect the human right. Fourth, Ridley Scott in Gladiator movie wants to rebel the social stratification.